Screening of a Novel Peptide Targeting the Proteoglycan-Like Region of Human Carbonic Anhydrase IX - Shoaib Rana; Felix Nissen; Thomas Lindner; Annette Altmann; Walter Mier; Juergen Debus; Uwe Haberkorn; Vasileios Askoxylakis (Molecular Imaging)
The extracellular domain of human carbonic anhydrase IX (CA IX) is extended by a proteoglycan-like region (PGLR). The aim of the present study was the development of novel molecules with specificity for PGLR, which may be used for tumor targeting and imaging. PGLR was chemically synthesized, and phage display biopanning was performed. The identified ligand PGLR-P1 was labeled with 125 I and characterized for target binding and metabolic stability. In vitro characterization included kinetic, competition, and internalization studies on CA IX–positive renal cell carcinoma SKRC 52 cells. The CA IX–negative cell lines HEK293 wt and BxPC3 were used as negative controls. In vitro binding experiments revealed an increasing affinity of 125 I-PGLR-P1 to SKRC 52 cells but not to negative control HEK293 wt and BxPC3 cells. Internalization studies indicated an exclusive cell membrane binding. Biodistribution analysis demonstrated a higher accumulation in SKRC 52 tumors than in most normal tissues after perfusion. In vivo blocking led to a significant decrease in tumor uptake. Our findings indicate that PGLR-P1 is a promising lead structure for the development of new peptide-based ligands targeting the PGLR of CA IX and reveal challenges that need to be considered for peptide-related molecular imaging.